Computational methods for analyzing genome-wide chromosome conformation capture data. (December 2018) - Nicoletti, Chiara; Forcato, Mattia; Bicciato, Silvio
Graphical abstract: Highlights: Chromosome conformation capture (3C) techniques allow investigating chromatin 3D architecture. Hi-C combines 3C techniques with high-throughput sequencing. The analysis of Hi-C data requires ad hoc computational methods. Newly emerging computational tools address critical issues in the analysis of Hi-C data. Abstract : In all organisms, chromatin is packed to fulfil structural constraints and functional requirements. The hierarchical model of chromatin organization in the 3D nuclear space encompasses different topologies at diverse scale lengths, with chromosomes occupying distinct volumes, further organized in compartments, inside which the chromatin fibers fold into large domains and short-range loops. In the recent years, the combination of chromosome conformation capture (3C) techniques and high-throughput sequencing allowed probing chromatin spatial organization at the whole genome-scale. 3C-based methods produce enormous amounts of genomic data that are analyzed using ad-hoc computational procedures. Here, we review the common pipelines and methods for the analysis of genome-wide chromosome conformation capture data, highlighting recent developments in key steps for the identification of chromatin structures.